The View of Islamic Law and Positive Law in Indonesia on The Alimentation of Children towards Parents - Taufika, Aisyah Nabila; Lukito, Ratno (DIKTUM: Jurnal Syariah dan Hukum, 2024)
Parents must care for their children based on Islamic and positive laws in Indonesia. Indeed, parents and children have an alimentation relationship, that is, a reciprocal relationship in maintenance or bread. However, in general, in society, the understanding of income is only imposed on parents to children, so there are many cases of parental neglect. So the question arises: What is the view of Islamic law and positive law in Indonesia regarding the provision of alimentation of children to parents? This research uses qualitative, juridical-normative research as its approach and descriptive as its research nature. The Qur'an, Hadith, the opinions of imams of madhab, laws and regulations, journals, books, and encyclopedias are sources for obtaining data, so this research is classified as literature research. The findings of this study on Islamic law and positive law in Indonesia indicate that children are obligated to support their parents under specific circumstances. According to Islamic law, this obligation arises when the parents are in need, and the child possesses the means to work or owns property. In positive law, the obligation arises when parents are in financial distress, require assistance, reside in their children's homes, among other conditions.